(3fUjMI GdfSGA GdeSdeGJ hPcQ GdehabGJ efgf hGdYGHOGJs - (3CMeO Hf CHj HcQ CMeO GdMfHdj GdbGOQj,J (B844 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi hab ef TGA ef YHGOg CeG HYO aEf Gddg JYGdi hdg GdMeO deG ef Ydi GdYHO HGdQMdg GdQGHYI Edi GdbGgQI s
(3BNQgG (B:s
(3hGbJOhG HgG hGYedhG HeG ajgG ef GdehGYX hGdQbGFb hGdRgOjGJ JadMhG hJfLMhG hHGddg GdJhajb s
(3CaGO GdeDda ai BNQgG Cfg GHJOC JCdja GdcJGH HGdbGgQI SfI (B833 (3Je RGO Ydjg HYO Pdc RjGOGJ MJi NQL ai UhQJg gPgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs